Development of an Interactive Exhibition to Enhance Digital Intelligence in Digital Security - Udomphol, Kawisara; Sriprasertpap, Khwanying (Ratchaphruek Journal, 2023)
The purposes of this quantitative model research were: 1) to develop a living exhibition promoting digital intelligence in digital security; 2) to assess the quality of a living exhibition; and 3) to study digital intelligence in digital security. The population used in the study were Srinakharinwirot University students who enrolled in the subject ES381 Media and Technology for Education and Learning course. The research tools were Live exhibition promoting digital intelligence in digital security, the assessment form, and the measurement form. The digital intelligence of visitors to the exhibition lives to promote digital intelligence in digital security. Data were analyzed by frequency, percentage, mean, and standard deviation. The results showed that: 1) the researcher designed a site map consisting of contents of 5 aspects of digital intelligence by using media, lectures, video games, and AR to be used in all aspects of the exhibition; 2) four areas that the educational technology experts rated that with the average score of 0.67 and 1.00; and 3) the results of the digital intelligence study had an average score of 5.32 10.00, 10.32, 9.00, and 8.81 respectively.